1977
DOI: 10.1007/bf00235500
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular free calcium and potassium during paroxysmal activity in the cerebral cortex of the cat

Abstract: Extracellular calcium and potassium activities (aCa and aK) as well as neuronal activity were simultaneously recorded with ion-sensitive electrodes in the somatosensory cortex of cats. Baseline aCa was 1.2-1.5 mM/l, baseline aK 2.7-3.2 mM/l. Transient decreases in aCa and simultaneous increases in aK were evoked by repetitive stimulation of the contralateral forepaw, the nucleus ventroposterolateralis thalami and the cortical surface. Considerable decreases in aCa (by up to 0.7 mM/l) were found during seizure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
224
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(246 citation statements)
references
References 19 publications
22
224
0
Order By: Relevance
“…According with this possibility, in some brain conditions characterized by increased neuronal activity and in certain pathological states such as seizures, ischemia, and hypoglycemia, Ca 2 + levels within the extracellular fluid of the brain are reduced and could potentially be sensed by CaSR (Heinemann et al, 1977). CaSR displays significant homology with metabotropic glutamate receptors (mGluRs) expressed in the brain (Nakanishi, 1992;Ruat et al, 1995), and it has been shown that some types of mGluRs, including mGluR3 and mGluR5, are activated not only by glutamate but also by extracellular Ca 2 + (Kubo et al, 1998), although the physiological relevance of this Ca 2 + -sensing property remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…According with this possibility, in some brain conditions characterized by increased neuronal activity and in certain pathological states such as seizures, ischemia, and hypoglycemia, Ca 2 + levels within the extracellular fluid of the brain are reduced and could potentially be sensed by CaSR (Heinemann et al, 1977). CaSR displays significant homology with metabotropic glutamate receptors (mGluRs) expressed in the brain (Nakanishi, 1992;Ruat et al, 1995), and it has been shown that some types of mGluRs, including mGluR3 and mGluR5, are activated not only by glutamate but also by extracellular Ca 2 + (Kubo et al, 1998), although the physiological relevance of this Ca 2 + -sensing property remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, this rhythmic GABAergic inhibition progressively decreases driven by the collapse of chloride gradients together with a desychronization of interneuronal firing (Derchansky et al, 2008;Dzhala et al, 2010;Gnatkovsky et al, 2008;Lasztoczi et al, 2009;Timofeev et al, 2002b;Viitanen et al, 2010). Then, the local EEG is dominated by large changes in extracellular potassium and calcium that contribute to sustained potentials and slow down oscillatory activity (Amzica et al, 2002;Heinemann et al, 1977;Kaila et al, 1997). Thus, the major cellular generators contributing to the broad range of HFO could evolve dynamically as a seizure progresses and cannot be ascribed to a unique source.…”
Section: Single Cell Dynamics During a Wide Range Of Hfo In Epileptogmentioning
confidence: 99%
“…Increases in [K + ] o are not unexpected during hypersynchronous activity such as that associated with an interictal discharge that is contributed by glutamatergic conductances leading to sustained action potential firing, and they have been well characterized both in in vivo (Heinemann et al, 1977;Krnjevic et al, 1980) and in vitro preparations Avoli et al, 1990). What is surprising in the 4AP model is that similar [K + ] o elevations can be observed concomitant to the glutamatergic-independent interictal discharges generated by neuronal networks during application of ionotropic glutamatergic receptor antagonists (Fig.…”
Section: [K + ] O Elevations and Slow Interictal Events-as Shown Inmentioning
confidence: 99%